Progranulin, a Major Secreted Protein of Mouse Adipose‐Derived Stem Cells, Inhibits Light‐Induced Retinal Degeneration. (14th November 2013) - Tsuruma, Kazuhiro; Yamauchi, Mika; Sugitani, Sou; Otsuka, Tomohiro; Ohno, Yuta; Nagahara, Yuki; Ikegame, Yuka; Shimazawa, Masamitsu; Yoshimura, Shinichi; Iwama, Toru; Hara, Hideaki
Abstract : The authors examined the protective effects of adipose‐derived stem cells and adipose‐derived stem cell‐conditioned medium (ASC‐CM) against retinal damage and identified the neuroprotective factors in ASC‐CM. The findings suggest that ASC‐CM and progranulin have neuroprotective effects in the light‐induced retinal‐damage model. Progranulin may be a potential target for the treatment of the degenerative diseases of the retina. Abstract : Adipose tissue stromal vascular fraction contains mesenchymal stem cells, which show protective effects when administered to damaged tissues, mainly through secreted trophic factors. We examined the protective effects of adipose‐derived stem cells (ASCs) and ASC‐conditioned medium (ASC‐CM) against retinal damage and identified the neuroprotective factors in ASC‐CM. ASCs and mature adipocytes were isolated from mouse subcutaneous tissue. ASCs were injected intravitreally in a mouse model of light‐induced retinal damage, and ASC injection recovered retinal function as measured by electroretinogram and inhibited outer nuclear layer, thinning, without engraftment of ASCs. ASC‐CM and mature adipocyte‐conditioned medium were collected after 72 hours of culture. In vitro, H2 O2 ‐ and light‐induced cell death was reduced in a photoreceptor cell line with ASC‐CM but not with mature adipocyte‐conditioned medium. In vivo, light‐induced photoreceptor damage was evaluated by measurement of outer nuclear layer thickness at 5 days after light exposure and by electroretinogram recording. ASC‐CM significantly inhibited photoreceptor degeneration and retinal dysfunction after light exposure. Progranulin was identified as a major secreted protein of ASCs that showed protective effects against retinal damage in vitro and in vivo. Furthermore, progranulin phosphorylated extracellular signal‐regulated kinase, cAMP response element binding protein, and hepatocyte growth factor receptor, and protein kinase C signaling pathways were involved in the protective effects of progranulin. These findings suggest that ASC‐CM and progranulin have neuroprotective effects in the light‐induced retinal‐damage model. Progranulin may be a potential target for the treatment of the degenerative diseases of the retina.